The market vs. the right to communicate - Wahl-Jorgensen, Karin (Javnost (Ljubljana), 2005)
The MacBride Report identified communication as a basic individual and collective right, and offered a range of recommendations to protect it. Among other things, the report highlighted the need to strengthen cultural identity, provide diversity of choice in media, reduce the commercialisation of communication, and remove obstacles to individuals' participation. This paper, based on interviews with journalists, argues that in the case of British local journalism, a market logic works against the right to communicate. The increasing dominance of resource-poor, chain-owned weekly newspapers has encouraged the rise of an anti-political journalism. I look at the anti-political tendencies of UK local journalism by focusing on campaigns, editorials and letters to the editor - the opinionated journalism through which local newspapers may advance social change. I argue that journalism-on-the-cheap, as practiced in local papers, becomes a journalism of consensus; one which has the power to enhance community solidarity but cannot question the status quo.
Keywords: Velika britanija; mass media; množični mediji; privatizacija; tržno gospodarstvo; lastništvo; obveščanje; pretok informacij; journalism; novinarstvo; objektivnost; svoboda tiska; svoboda informiranja; svoboda govora